Star wars 1 the phantom menace - Lucas, George; McCallum, Rick.; Twentieth Century Fox Home Entertainment; Lucas Film. (Universal City, Calif. Twentieth Century Fox Home Entertainment, 2015)
When Jedi apprentice Obi-Wan Kenobi and his Jedi Master Qui-Gon Jinn end up stranded on planet Tatooine, they discover young Anakin Skywalker, who has the power of the Force.
Originally released as a motion picture in 1999.
Director of photography, David Tattersall ; edited by Paul Martin Smith, Ben Burtt ; music by John Williams ; animation director, Rob Coleman.
CHV rating: PG.
VCD
Keywords: Vader, Darth -- (Fictitious character) -- Drama; Kenobi, Obi-Wan -- (Fictitious character) -- Drama; Jinn, Qui-Gon -- (Fictitious character) -- Drama; Vader, Darth -- (Fictitious character); Jinn, Qui-Gon -- (Fictitious character); Kenobi, Obi-Wan -- (Fictitious character)